Integration of leadership training for graduate and medical students engaged in translational biomedical research: Examining self-efficacy and self-insight. Issue 1 (6th June 2018) - Chao, Celia; Wooten, Kevin; Spratt, Heidi; Sarraj, Huda; Aronson, Judith; Hommel, Jonathan; Ungerleider, Ross; Ungerleider, Jamie D.; Hellmich, Mark R.
Abstract : Introduction: Formal training in team leadership is not taught in biomedical research graduate training programs or medical schools. Methods: We piloted a Leadership Training Workshop for graduate biomedical and medical students enrolled in our Interprofessional Research Design Course. Results: The Kane–Baltes self-efficacy survey demonstrated improved leadership skills (median scores pretraining and post-training were 71 and 76.6; paired t -test, p =0.04). Conclusions: Most students demonstrated significant improvement in self-awareness pertaining to their own innate leadership styles.